Uncovering transgression in the textiles collection of the National Army Museum Te Mata Toa : a research report presented in partial fulfilment of the requirements for the degree of Master of Arts in Museum Studies, at Massey University, Manawatū, New Zealand - Harrison, Philippa A.E. (Massey University, 2021)
This research centres on the textiles collection of the National Army Museum Te Mata Toa (NAM) which encompasses military clothing and associated items, holding examples from the New Zealand Wars of the 19th century to the present. The collection overall is visually conventional and male-centric with a noticeably lower proportion of women-related textiles, these mainly comprising World War II nursing and other service uniforms, such as those of the Women’s Land Service. The Museum’s displays reflect this understated female narrative. The intention of my research was to question whether a patriarchal view has caused women-related garments in NAM’s textiles holding to be overlooked, resulting in less focus on collecting and researching these textiles. Despite their layered social history contributions being directly related to New Zealand’s military life, had a lack of professional training and best practice knowledge adversely affected the textiles collection? To consider the question I have applied Laura Mulvey’s “male gaze” theory of filmic spectatorship (ways of viewing) to the museum textiles context. The theory argues that whereas men are positioned as protagonists and spectators, actively controlling narratives and events, women are peripheral, dependent, the spectated upon. However, women are also transgressive, capable of disturbing a male world view (Mulvey, 1975, p.18). Applying this theme to textiles appeared logical as I noticed non-conventional or aberrant female-related objects emerging during curatorial work. Three dissonant objects, purposefully selected, are the focus of a qualitative research framework using case studies within a specifically NAM context. Examples from the uniforms, souvenirs and comforts categories follow the prescribed steps of Jules David Prown’s material culture method (1982) for framing the case studies, and semi-structured interviews were also conducted. The findings reveal that collecting habits have caused a lesser female narrative in the textiles collection, despite the case study objects’ ability to evoke strong feelings and memories. Through the practices undertaken in relationship to objects themselves, the research also makes a case for systematic application of material culture studies frameworks to collection management and collection research.
Keywords: 430202 Critical heritage, museum and archive studies